Degradasi Zat Warna Indigosol Red Ir Menggunakan Metode Sonolisis Dengan Bantuan Katalis ZnO - Indah Humaira Saragih; Hary Sanjaya (Departemen Kimia FMIPA UNP, 2023)
This research was conducted for the modeling degradation process of Indigosol Red Ir dye using the sonolysis method with the help of a ZnO catalyst. This study aims to determine the optimum mass addition of ZnOÂ catalyst in the degradation process of Indigosol Red Ir dye. Sonolysis method using an ultrasound with frequency 47 kHz. The results of the percent degradation were seen from the absorbance measurement using a uv-vis spectrophotometer at a maximum wavelength of 510.2 nm. The results showed that the addition of the optimum mass of ZnO catalyst was 0.05 grams with a degradation percentage of 93.72%.